Postinfluenza Vaccination Idiopathic Thrombocytopenic Purpura in Three Elderly Patients - Joji Nagasaki; Masahiro Manabe; Kentaro Ido; Hiroyoshi Ichihara; Yasutaka Aoyama; Tadanobu Ohta; Yoshio Furukawa; Atsuko Mugitani (Case Reports in Hematology)
The etiologies of secondary idiopathic thrombocytopenic purpura (ITP) include infection, autoimmune disease, and immunodeficiency. We report the cases of three elderly patients who developed ITP after receiving influenza vaccinations. The platelet count of an 81-year-old woman fell to 27,000/μL after she received an influenza vaccination. A 75-year-old woman developed thrombocytopenia (5,000 platelets/μL) after receiving an influenza vaccination. An 87-year-old woman whose laboratory test values included a platelet count of 2,000/μL experienced genital bleeding after receiving an influenza vaccination. After Helicobacter pylori (HP) eradication or corticosteroid treatment, all of the patients’ platelet counts increased. Influenza vaccination is an underlying etiology of ITP in elderly patients. HP eradication or corticosteroid treatment is effective for these patients. Clinicians should be aware of the association between ITP and influenza vaccinations.